Implementasi Muatan Lokal pada Pembelajaran Program Paket C - Cahyaningtyas, Ade Wahyu; Sutarto, Joko (Journal of Nonformal Education and Community Empowerment, 2021)
This study aims to describe the planning, implementation, evaluation and collaboration of the implementation of local content in the learning of package C programs at PKBMMitra Harapan Semarang. This study uses a qualitative approach with qualitativedescriptive methods. The subjects in this study were managers, tutors, and students. Datacollection techniques are done through interviews, observation, and documentation. Thedata validity technique uses source and method triangulation. Data analysis techniquesare done through data reduction, data presentation, and verification or drawingconclusions. The results showed that the curriculum used was the 2013 curriculum.Learning materials were designed by RPP dan Silabus. Learning resources used modulesand teaching materials in accordance with the curriculum. Recruitment of students isdone by easing the registration requirements. Tutor recruitment is selected according toexpertise and standards. The facilities and infrastructure to support learning aresufficient. Based on the results of the study it can be concluded that the implementation oflocal content in the learning of package C programs at PKBM Mitra Harapan Semaranghas been well designed and implemented. Suggestions in this research are expected to addfacilities and infrastructure as well as learning media to create an interesting and notboring learning atmosphere.